Occupational outlook for specialist dental nurses (口腔专科护士的职业展望) - WU Xuan (吴宣); GAN Ling (甘泠); DING Shanshan (丁珊珊) (中西医结合护理)
Oral health is a hot issue of public concern. The cultivation of specialist dental nurses may help to alleviate the contradiction between supply and demand of oral healthcare service, and help health professionals deliver better services of oral preventive care. This paper summarized the current situation of cultivation and future of the specialist dental nurses, in order to provide reference for the development of specialist nurse training system. (口腔健康是人民群众关注的热点问题, 口腔专科护士的培养将有助于缓解口腔保健供求间的矛盾, 更好地开展居民口腔预防保健工作。本文就目前口腔专科护士的培养现状以及未来职业发展进行了总结和分析, 以期为进一步规范专科护士培养体系提供参考。)